2019
DOI: 10.1038/s41467-019-09111-2
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobinopathy is an adult-onset autosomal dominant myopathy with characteristic sarcoplasmic inclusions

Abstract: Myoglobin, encoded by MB , is a small cytoplasmic globular hemoprotein highly expressed in cardiac myocytes and oxidative skeletal myofibers. Myoglobin binds O 2, facilitates its intracellular transport and serves as a controller of nitric oxide and reactive oxygen species. Here, we identify a recurrent c.292C>T (p.His98Tyr) substitution in MB in fourteen members of six European families suffering from an autosomal dominant progressive myopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 64 publications
4
13
0
Order By: Relevance
“…From the intercept of the linear plots, the dissociation rate constants (k off ) were obtained allowing calculation of the dissociation constants, K D (= k off /k on ), which resulted 3.7 and 10.9 µM, respectively (Table 1). Ferric H98Y MB therefore features a lower affinity for cyanide compared with the wt protein, as previously observed for molecular oxygen [7].…”
Section: Kinetics Of Cn − Bindingsupporting
confidence: 74%
“…From the intercept of the linear plots, the dissociation rate constants (k off ) were obtained allowing calculation of the dissociation constants, K D (= k off /k on ), which resulted 3.7 and 10.9 µM, respectively (Table 1). Ferric H98Y MB therefore features a lower affinity for cyanide compared with the wt protein, as previously observed for molecular oxygen [7].…”
Section: Kinetics Of Cn − Bindingsupporting
confidence: 74%
“…The Danish man first manifested in an airplane, so that the possibility of “myoglobinopathy” was considered. A recently reported disease entity myoglobinopathy shows progressive chronic myopathy with an autosomal-dominant trait [ 6 ], but an acute disease as seen in the present case has not been described.…”
Section: Discussionmentioning
confidence: 66%
“…Weekly interdisciplinary meetings between the clinical, scientific, neuropathological, and research teams were vital for maximizing diagnostic success and triage of unsolved patients to research projects, as reported by others . This process facilitated the discovery of six new disease genes …”
Section: Discussionmentioning
confidence: 97%
“…10,20,21 This process facilitated the discovery of six new disease genes. [22][23][24][25][26][27] Use of a large panel, rather than exome sequencing, provided the optimal balance between cost and diagnostic success. Panel sequencing costs less than exome sequencing and has only 4-11% lower success rates than exomes restricted to known genes.…”
Section: Discussionmentioning
confidence: 99%